2017
DOI: 10.3354/aei00214
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide and methane fluxes across the sediment-water interface in different grass carp Ctenopharyngodon idella polyculture models

Abstract: Benthic fluxes of carbon dioxide (CO 2 ) and methane (CH 4 ) were evaluated in grass carp Ctenopharyngodon idella (G), silver carp Hypophthalmichthys molitrix (S), and bighead carp Aristichthys nobilis (B) polyculture systems, to which topmouth culter Erythroculter ilishaeformis (T), Pacific white shrimp Litopenaeus vannamei (P), or common carp Cyprinus carpio (C) were added. These systems, GSBT, GSBP, and GSBC, respectively, were monitored over 5 mo (May to September 2014). The presence of L. vannamei and C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 63 publications
2
12
1
Order By: Relevance
“…Limitation of algal growth due to fish‐enhanced turbidity is also a common phenomenon in aquacultures (Rahman et al., ). Other studies found fish‐induced increases in water column CO 2 concentration as well (Rahman et al., ; Xiong et al., ). In hypertrophic fish cultures, however, the CO 2 emissions tend to be much higher than those we found in our study (Chen et al., ).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Limitation of algal growth due to fish‐enhanced turbidity is also a common phenomenon in aquacultures (Rahman et al., ). Other studies found fish‐induced increases in water column CO 2 concentration as well (Rahman et al., ; Xiong et al., ). In hypertrophic fish cultures, however, the CO 2 emissions tend to be much higher than those we found in our study (Chen et al., ).…”
Section: Discussioncontrasting
confidence: 84%
“…We found that in our systems, where water column O 2 concentrations remained above 3 mg/L during the entire study period, fish strongly reduced CH 4 emissions, contrasting other studies reporting high CH 4 emission rates for fish ponds (Datta et al., ; Frei et al., ), which the authors attribute to fish‐induced lowering of surface water O 2 concentrations (Xiong, Wang, Guo, Liu, & Dong, ). These low O 2 concentration may be caused by fish respiration, reduced phytoplanktonic photosynthesis due to high turbidity, or enhanced aerobic organic matter oxidation due to bioturbation.…”
Section: Discussionmentioning
confidence: 99%
“…The peak of CH 4 flux recorded in the main ponds in May can be explained by sediment bioturbation by carp along with wind speed. At the beginning of the growing season, the feeding behaviour of carp enhances the release of CH 4 accumulated in sediment during the previous growing season and winter (Bhattacharyya et al 2013, Xiong et al 2017. The average wind speed in May was higher over the main ponds (2.3 ± 0.5 m s −1 ) than above nursery ponds (1.0 ± 0.5 m s −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In some countries, fishponds are an important component of lentic ecosystems (Pechar 2000). Fishponds occupy a surface area of 1200 km 2 in France, 410 km 2 in the Czech Republic, 420 km 2 in Germany, 25 669 km 2 in China, and 87 500 km 2 worldwide (Pokorný & Hauser 2002, Four et al 2017, Xiong et al 2017). In addition to rearing fish, fishponds provide ecosystem functions such as flood regulation along with retention of water, sediments, organic matter, nutrients, and micropollutants and may be important in maintaining bio diversity (Oertli et al 2005, Boyd et al 2010, Gaillard et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the boundary between the water column and sediments, i.e. the sediment‐water interface (SWI), plays a critical role in the production, transfer, circulation, and storage of CH 4 in aquaculture ponds (Xiong et al, ). While the rapid development of the aquaculture industry has stimulated researches examining CH 4 biogeochemistry in aquaculture systems, most of the previous studies only focused on CH 4 exchange across the water‐air interface and its influencing factors (e.g., Chen et al, ; Hu et al, , ; Yang et al, ; Yang, Bastviken, et al, ; P. Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%